Electro-optic photonic circuits : from linear and nonlinear waves in nanodisordered photorefractive ferroelectrics /: from linear and nonlinear waves in nanodisordered photorefractive ferroelectrics. ([2019]) - Di Domenico, Giuseppe
No abstract available